IPTEKS AKUNTANSI SUMBER DAYA MANUSIA PADA PENCAPAIAN TARGET CONSUMER LOAN - Johannes, Christy Handayanie; Kindangen, Wulan D. (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
Human Resources are important assets, Accounting for human resources Human Resource Accounting is an acknowledgment that people constitute human capital and human assets. The economic theory of human capital is based on the concept that humans have the skills, experience, and knowledge which are forms of capital, which are called "human capital managementthat must be owned in the world of work. Although now the world is getting more sophisticated but if there is no Human intervention, of course the machine will not work well. As in the world of work the Consumer Loan Area Of Manado of course, is in desperate need of Human Resources, in achieving loan credit. Consumer Loan Area Manado customers must maintain and balance the development of local Human Resources. To reach the target, of course, the Consumer Loan has its own way of empolying Human Resources called sales. Sales work to product sales and must understand marketing management in Consumer Loansfor example, collaterals from each registered developer. And sales gave developers an offer so that developers would also want to join the Bank Mandiri Consumer Loan In Manado. However, the sales must also obey and understand the regulations in the Consumer Loan.and if Human Resources work well in the company where they work. Then each gets a profit, for example. Sales get a lucrative bonus from the company because it has helped to achieve the target of Home Ownership Loans. And the company also received a plus because it achieved satisfactory results.and applying good principles and governance with good corporate governanceKeywords: human capital management, local human resource development,marketing management